Vertigo and Dizziness in the Elderly - Fernández, Lara; Breinbauer, Hayo A.; Delano, Paul Hinckley (Frontiers in Neurology, 2015)
The prevalence of vertigo and dizziness in people aged more than 60 years reaches 30%, and due to aging of world population, the number of patients is rapidly increasing. The presence of dizziness in the elderly is a strong predictor of falls, which is the leading cause of accidental death in people older than 65 years. Balance disorders in the elderly constitute a major public health problem, and require an adequate diagnosis and management by trained physicians. In the elderly, common causes of vertigo may manifest differently, as patients tend to report less rotatory vertigo and more nonspecific dizziness and instability than younger patients, making diagnosis more complex. In this mini review, age-related degenerative processes that affect balance are presented. Diagnostic and therapeutic approaches oriented to the specific impaired system, including visual, proprioceptive, and vestibular pathways are proposed. In addition, presbystasis -the loss of vestibular and balance functions associated with aging-, benign paroxysmal positional vertigo, and stroke (in acute syndromes) should always be considered.